Globalizing justice the ethics of poverty and power - Miller, Richard W., 1945- (Oxford : Oxford University Press, 2010)
'Globalizing Justice' provides philosophical foundations for political responsibility, an agenda of policies for responding to major global problems, and a distinctive appraisal of 'the American empire'. It offers realistic stratefgies for global social movement that helps to move humanity toward global cooperation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Globalization -- Moral and ethical aspects; Poverty -- Moral and ethical aspects; Power (Social sciences); Globalization -- Economic aspects; Globalization -- Philosophy